Activating stereotypes through sports media: effects of racialized athlete portrayals on subsequent social judgments. Issue 2 (15th March 2023) - Ash, Erin; Cranmer, Gregory A.; Pool, Rebecca N.
ABSTRACT: This research investigates whether stereotypes activated by common media portrayals of Black athletes that emphasize physicality influence social judgments outside the sporting context. Results of a 2 (athlete race) X 2 (athlete frame) between-subjects experiment indicated that when an athlete was framed in terms of physical attributes, participants evaluated a suspect in a subsequent news story based on overlapping qualities related to criminality, regardless of athlete race. However, when an athlete was described in terms of their mental skills, physical qualities were more likely to be ascribed to a Black athlete and to impact evaluations of the crime suspect.